Deciphering English Vowel Digraphs: Pronunciation Challenges in the EFL Classroom - Putra, Rizky Anugrah (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2023)
The inconsistency in predicting pronunciation based on English alphabetic spelling is a persistent challenge in English Language Teaching (ELT). This study investigates how 42 first-semester English as a Foreign Language (EFL) students predict sounds represented by <oa> and <oo> digraphs. Using stimuli from a familiar vocabulary list, 408 instances of mispronunciation were identified from 1260 speech data, with 386 as interlingual errors and 24 as intralingual errors. The study concludes that EFL learners heavily rely on their native language (L1) knowledge in perceiving and producing speech in the target language(L2). This research highlights the challenges EFL students face in mastering English pronunciation, emphasizing the need for effective language instruction strategies.